Analysis of Senior High School Mathematics Teachers’ Perception of The Application of STEM-Based Learning - Sari, Fitri Aida; Juandi, Dadang (Mathematics Dept, Math. and Science Faculty, Universitas Negeri Semarang, 2022)
STEM-based learning is a learning approach that integrates science, technology, engineering, and mathematics in a lesson so that students have critical thinking skills and they can solve problems creatively, and consequently, students will have a selling point in the labor market. This study aims to determine the senior high school teachers’ perception of the application of STEM-based learning. This study is descriptive qualitative research that describes the actual facts and circumstances about the senior high school teachers’ perception of the application of STEM-based learning. The subjects of this study were senior high school mathematics teachers in Serang City and Serang District. The research instrument was an open questionnaire consisting of 21 questions. After being given an open questionnaire, observations and interviews were conducted. Based on the results of the analysis of the open questionnaire given, it is known that senior high school mathematics teachers still lack information about STEM-based learning. Not all teachers know about STEM-based learning, in fact there are some teachers who have just heard the term. Therefore, socialization and training are needed so that all teachers have a good understanding of STEM-based learning.Pembelajaran berbasis STEM merupakan suatu pendekatan pembelajaran yang mengintegrasikan sains, teknologi, rekayasa, dan matematika dalam suatu pembelajaran yang bertujuan agar siswa memiliki keterampilan berpikir kritis dan dapat memecahkan masalah secara kreatif, sehingga mereka memiliki nilai jual di pasar tenaga kerja. Penelitian ini bertujuan untuk mengetahui persepsi guru matematika SMA mengenai penerapan pembelajaran berbasis STEM. Penelitian ini merupakan penelitian deskriptif kualitatif yang menggambarkan fakta dan keadaan sebenarnya tentang persepsi guru matematika SMA mengenai penerapan pembelajaran berbasis STEM. Subjek penelitian ini adalah guru mata pelajaran matematika SMA di Kota Serang dan Kabupaten Serang. Instrumen penelitian berupa angket terbuka yang terdiri dari 21 pertanyaan. Setelah diberikan angket terbuka kemudian dilakukan observasi serta wawancara. Berdasarkan hasil analisis terhadap angket terbuka yang diberikan, diketahui bahwa guru matematika SMA masih kekurangaan informasi mengenai pembelajaran berbasis STEM. Tidak semua guru mengetahui tentang pembelajaran berbasis STEM, bahkan masih ada guru yang baru mendengar istilah tersebut. Oleh karena itu, diperlukan sosialisasi dan pelatihan agar seluruh guru memiliki pemahaman yang baik mengenai pembelajaran berbasis STEM.